All optical, high contrast absorptive modulation in an asymmetric Fabry-Perot etalon - HEGARTY, JOHN (American Institute of Physics, 1991)
We report a 27:l switching contrast ratio with 2.5 mW of power in an asymmetric Fabry- Perot Ctalon. The modulation is achieved by optical saturation of the excitonic absorption profile of a 95 A GaAs/AlGaAs multiple quantum well structure grown on a high-reflectivity dielectric stack mirror.
PUBLISHED
Keywords: Physics